Socio‐Economic Interest of Treated Wastewater Reuse in Agricultural Irrigation and Indirect Potable Water Reuse: Clermont‐Ferrand and Cannes Case Studies' Cost–Benefit Analysis. (14th December 2017) - Declercq, Rémi; Loubier, Sébastien; Condom, Nicolas; Molle, Bruno
Abstract: Unlike many structuring projects, treated wastewater reuse projects are rarely subjected to economic analysis. And when they are, the social and environmental benefits and costs are often not accounted for or are not properly quantified. Here we show that the widely used cost–benefit analysis method showing the profitability of a project from the whole of the community's point of view can be adapted to treated wastewater reuse projects. The remaining evaluation difficulties are more due to the system's complexity rather than its methodological limits. Indeed, the operator must be able to understand, formalize and imagine constraints and risks associated with different domains such as urbanism, agriculture, climate, hydrology and trade. Remaining uncertainties over key parameter values can, however, be properly considered through scenarios and/or stochastic approaches. We illustrate the implementation of this methodological approach with two case studies: Clermont‐Ferrand where treated wastewater is reused by a collective irrigation network; and Cannes where surface and groundwater recharge can enable indirect reuse for multiple purposes including indirect potable water production. These two French case studies highlight how economic analysis, dealing with uncertainties, can support decision making. Copyright © 2020 John Wiley & Sons, Ltd. Résumé: Les projets de réutilisation des eaux usées traitées font rarement l'objet d'analyses économiques. Lorsque c'est le cas, les coûts et bénéfices sociaux et environnementaux ne sont pas correctement pris en compte ou quantifiés. Nous montrons ici que la méthodologie d'analyse coût–bénéfices (ACB) permettant d'évaluer la rentabilité d'un projet à l'échelle d'un territoire peut être adaptée à l'évaluation de projets de réutilisation des eaux usées traitées. La méthodologie employée est bien maitrisée et les difficultés de mise en œuvre sont davantage liées à la complexité du système. L'opérateur doit en effet être en mesure de comprendre, de formaliser et d'imaginer les contraintes et les risques associés à différents domaines tels que l'urbanisme, l'agriculture et l'hydrologie. Les incertitudes résiduelles sur les valeurs de paramètres clés peuvent être prises en compte par l'étude de différents scénarios et/ou par des approches stochastiques. Nous illustrons cette approche à travers les études de cas français de Clermont‐Ferrand où des eaux usées traitées sont réutilisées par un réseau collectif d'irrigation, et de Cannes où la recharge de milieux permet la réutilisation indirecte pour différents usages, dont la production indirecte d'eau potable. Ces études de cas illustrent comment l'analyse économique peut aider à la prise de décision. Copyright © 2020 John Wiley & Sons, Ltd.